Housewives' Self-esteem and their Husbands' Success: A Comparative Study among the Various Caste Groups in Pokhareli Women - Paudel, Deepak Raj (Himalayan Journal of Sociology and Anthropology, 2011)
This paper examines the relationship between self esteem of housewives with respect to some selected socioeconomic variables, namely; marital status, husband’s income, husband’s occupation, husband’s physical attraction, women’s own intelligence and women’s physical attraction with a sample of 240 Pokherli married women. The study compares whether the self-esteem of women and other different factors is different among the various caste groups. A comparison is also made between professional women and housewives. Self-esteem of women is signiicantly different among the various caste groups with the highest in Magar and Gurung women. Professional women are more conscious than housewives in all aspects of husband’s success. This study tests the common assertion that women, having reasonably higher income housewives experience their husbands’ success. Husbands’ success does positively affect a housewife’s self esteem, but only indirectly, through its effect on perceived marital success. Only husband’s income has a direct positive effect on self esteem, while other successes of the husband actually lower her self esteem. Since marriage is traditionally a basis for a woman’s identity, successful marriage increases her feelings of worth. However, the speciic role arrangements may reduce her feelings of personal competence. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4668 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 61-76